Mendorong Produktivitas Kerja Melalui Peran Pelatihan dan Kepuasan Kerja Dengan Komitmen Organisaional Sebagai Intervening Penelitian Pada Karyawan Industri Genteng di Kebumen - permata, permata; Harry Cahyono; Julinha Betty Guterres Riu (Universitas Serang Raya, 2023)
This study aims to investigate the effect of job training and job satisfaction on work productivity, with organizational commitment as an intervening variable. This research is a quantitative research with employee respondents in the tile industry in Kebumen Regency. Data is obtained with questionnaire distribution instruments, which then the collected data is processed with the help of AMOS software and Structural Equation Modeling (SEM) analysis tools. The results of the analysis show that the level of job satisfaction has a significant positive influence on employee work productivity, with organizational commitment acting as an intervening variable.On the other hand, research findings show that job training does not have a significant impact on organizational commitment or employee work productivity. This suggests that, although job training can improve employees' skills and knowledge, other factors may be more dominant in influencing organizational commitment and work productivity in the context of the tile industry in Kebumen District. The conclusion of this study highlights the importance of job satisfaction management as a strategy to increase employee work productivity. With the increase in job satisfaction, it can be expected that organizational commitment also increases, thus having a positive impact on work productivity.